Wireless Technology and Spectrum Demand : Advanced Wireless Services. (U.S. Congressional Research., 2007)
Examines issues related to the deployment of third-generation and fourth-generation wireless technologies. Discusses development of and growing demand for wireless technology; and examines approaches for expanding broadband wireless access to the Internet, including municipal deployment of broadband, use of unlicensed spectrum, and fair access legislation. Summarizes bills in the 110th Congress.